Workplace Bullying, Job Stress, Intent to Leave, and Nurses' Perceptions of Patient Safety in South Korean Hospitals. Issue 5 (September 2016) - Oh, Hyunjin; Uhm, Dong-choon; Yoon, Young Joo
Abstract : Background: Negative work environments influence the ability of nurses to provide optimal patient care in a safe environment. Aim: The purpose of the study was to test a model linking workplace bullying (WPB) and lateral violence (LV) with job stress, intent to leave, and, subsequently, nurse-assessed patient adverse outcomes (safety issues). Design: This descriptive-correlational study examined the relationships between study variables and used a structural equation model to test the validity of the proposed theoretical framework. Methods: A convenience sample of 508 clinical nurses working in eight general hospitals in Daejeon, South Korea, completed a questionnaire on measures of WPB, LV, job stress, intent to leave, and nurse-assessed patient safety. Analysis of moment structures was used to estimate a set of three models with competing measurement structures for WPB and LV and the same structural model. Akaike Information Criterion was used for model selection. Results: Among the three proposed models, the model with complex factor loadings was selected (WPB and LV were both associated with verbal abuse and physical threat). WPB directly and indirectly influenced nurse-assessed patient safety. Job stress directly influenced intent to leave, and intent to leave directly influenced nurse-assessed patient safety. Conclusions: The results of the study support the proposition that WPB, job stress, and intent to leave may be associated with nurse-perceived adverse outcomes (patient safety issues) in hospitals. Nurse perceptions of WPB were associated with nurse-assessed patient safety outcomes (adverse events) directly and through mediating job stress and intent to leave. LV was not associated with the mediators or nurse-assessed adverse outcomes (safety).